Clinical Treatment of Perioperative Disseminated Intravascular Coagulation in Patients Who Underwent Gastrointestinal and Hepato-Biliary-Pancreatic Surgery. Issue 4 (April 2023) - Tomioka, Kodai; Aoki, Takeshi; Matsuda, Kazuhiro; Enami, Yuta; Fujimori, Akira; Koizumi, Tomotake; Kusano, Tomokazu; Date, Hiromi; Yamashita, Takeshi; Ariyoshi, Tomotake; Goto, Satoru; Yamazaki, Kimiyasu; et al.
Background: It is unclear how effective recombinant thrombomodulin (rTM) treatment is in disseminated intravascular coagulation (DIC) during the perioperative period of gastrointestinal and hepato-biliary-pancreatic surgery. The current study aimed to evaluate the therapeutic outcomes of rTM for perioperative DIC. Methods: We enrolled 100 consecutive patients diagnosed with perioperative DIC after gastrointestinal surgery, and hepato-biliary-pancreatic including emergency procedures, between January 2012 and May 2021. Patients received routine rTM treatment immediately after DIC diagnosis. Then, the DIC, Sequential Organ Failure Assessment (SOFA), and Acute Physiology and Chronic Health Evaluation (APACHE) II scores were calculated and used for evaluation. The outcomes of rTM treatment and the predictors of survival were evaluated. Results: The causative diseases of DIC were as follows: perforated peritonitis, n = 38; intestinal ischemia, n = 23; intra-abdominal abscess, n = 13; anastomotic leakage, n = 7; pneumonia, n = 7; cholangitis, n = 4; and others, n = 6. The 30-day mortality rate was 18.0%. There were significant differences in the platelet count (13.78 vs 10.41, P = .032) and the SOFA score (5.22 vs 9.89, P<.0001) at the start of DIC treatment between the survivor and non-survivor groups (day 0). The survivor group had a significantly lower DIC score (3.13 vs 4.93, P = .0006) and SOFA score (4.94 vs 12.14, P < .0001) and a higher platelet count (13.50 vs 4.34, P < .0001) than the non-survivor group on day 3. Conclusions: Comprehensive and systemic treatment is fundamentally essential for DIC, in which rTM may play an important role in the treatment of perioperative DIC.